Sistem Bangun Kontrol Kapal Menggunakan Metode LoRa - Reza Putra Susanto; Diana Alia; Agus Prawoto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Unmanned Surface Vehicle (USV) is an unmanned vehicle that is currently being developed in Indonesian waters for the purposes of depth surveys in waters that combine autonomous navigation frames, environmental sensors, multibeam echosounders to collect topography, temperature, and other data that are utilized for the world of shipping. Researchers tested an unmanned ship tool that can move automatically and can determine the direction to a predetermined location. Output. The test results show that the unmanned ship can walk to the planned route. This unmanned ship is equipped with a Micro Air M10G GPS sensor, LoRa Sensor, Arduino Mega 2560 Pro Sensor... In testing as many as 15x experiments were carried out including 10x experiments carried out to turn right and 5x experiments with turning left. The experiments carried out were very effective and according to what had been planned, but there were 4x experiments that had differences from 11x experiments due to water waves and winds that were too large so that the ship was unstable.